PsycEXTRA Dataset 2005
DOI: 10.1037/e470462008-001
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Rhode Island probation specialized domestic violence supervision unit

Abstract: Prepared by

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
20
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 17 publications
6
20
0
Order By: Relevance
“…This is remarkably similar to the figure of 17% in another English police force area (Bland & Ariel, 2015). American research, using perpetrator samples derived from criminal justice rather than police data, has resulted in slightly higher prevalence rates of serial domestic abuse, ranging from 28% of probationers within a one-year period (Klein, Wilson, Crowe, & DeMichele, 2005) to 43% of persons arrested for violating a civil restraining order over a six-year period (Bocko, Cicchetti, Lempicki, & Powell, 2004). In sum, existing research indicates that serial abusers constitute a sizeable minority of the total number of domestic abusers known to criminal justice agencies at any one time, but these estimates vary according to the data source and the definition being used.…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…This is remarkably similar to the figure of 17% in another English police force area (Bland & Ariel, 2015). American research, using perpetrator samples derived from criminal justice rather than police data, has resulted in slightly higher prevalence rates of serial domestic abuse, ranging from 28% of probationers within a one-year period (Klein, Wilson, Crowe, & DeMichele, 2005) to 43% of persons arrested for violating a civil restraining order over a six-year period (Bocko, Cicchetti, Lempicki, & Powell, 2004). In sum, existing research indicates that serial abusers constitute a sizeable minority of the total number of domestic abusers known to criminal justice agencies at any one time, but these estimates vary according to the data source and the definition being used.…”
Section: Introductionsupporting
confidence: 58%
“…However, extant research on domestic abuse has found that abusers who go on to abuse new partners are not substantially different from those who reabuse the same partner (i.e., the profiles of serial and repeat abusers are more alike than different). There is some evidence that serial abusers tend to be younger and less likely to be married (Adams, 1999;Klein et al, 2005) but, perhaps contrary to popular opinion, extant research does not indicate that serial abusers are the most dangerous, particularly when they are compared to repeat abusers. More detailed research, especially studies designed to capture information about victim sequelae, would be beneficial for establishing whether serial domestic abusers are a distinctive group and indeed whether the nature of their offending is experienced by victims as more harmful.…”
Section: Correlatesmentioning
confidence: 98%
“…In an effort to answer this question, the National Institute of Justice funded research to evaluate the specialized probation supervision of abusers across one state, Rhode Island (Klein, Wilson, Crowe, & DeMichele, 2005). This article describes the researchers' findings.…”
mentioning
confidence: 96%
“…In a study in Colorado Springs, researchers found that police almost never identified stalking, although researchers documented it in 18% of all of the domestic violence incident reports filed (Tjaden & Thoennes, 2001). Across Rhode Island, although the state's 38 police departments did make some stalking arrests, for each stalking case identified, they missed 40, according to researchers (Klein, Wilson, Crowe, & DeMichele, 2005). One of the reasons it appears that law enforcement (and prosecutors) appear to not be taking stalking more seriously, in addition to its being more difficult to document, is that it is typically characterized as a nonviolent, certainly nonlethal offense.…”
Section: Domestic Violence Damage Delineatedmentioning
confidence: 90%